Acute Hemodynamic Responses to Enhanced External Counterpulsation in Patients With Coronary Artery Disease - Zhang, Yahui; Chen, Ziqi; Mai, Zhouming; Zhou, Wenjuan; Wang, Hui; Zhang, Xiaodong; Wei, Wenbin; Du, Jianhang; Wu, Guifu (Frontiers in Cardiovascular Medicine, 2021)
Purpose: Enhanced external counterpulsation is a non-invasive treatment that increases coronary flow in patients with coronary artery disease (CAD). However, the acute responses of vascular and blood flow characteristics in the conduit arteries during and immediately after enhanced external counterpulsation (EECP) need to be verified. Methods: Forty-two patients with CAD and 21 healthy controls were recruited into this study to receive 45 min-EECP. Both common carotid arteries (CCAs), namely, the left carotid (LC) and right carotid (RC), the right brachial (RB), and right femoral (RF) artery were imaged using a Color Doppler ultrasound. The peak systolic velocity (PSV), end-diastolic velocity (EDV), mean inner diameter (ID), resistance index (RI), and mean flow rate (FR) were measured and calculated before, during, and after the 45 min-EECP treatment. Results: During EECP, in the CCAs, the EDV was significantly decreased, while the RI was markedly increased in the two groups (both P < 0.01). However, immediately after EECP, the RI in the RC was significantly lower than that at the baseline in the patients with CAD (P = 0.039). The FR of the LC was markedly increased during EECP only in the CAD patients (P = 0.004). The PSV of the patients with CAD was also significantly reduced during EECP (P = 0.015) and immediately after EECP (P = 0.005) compared with the baseline. Moreover, the ID of the LC, RB, and RF was significantly higher immediately after EECP than that at the baseline (all P < 0.05) in the patients with CAD. In addition, they were also higher than that in the control groups (all P < 0.05). Furthermore, by the subgroup analysis, there were significant differences in the FR, PSV, and RI between females and males during and immediately after EECP (all P < 0.05). Conclusions: Enhanced external counterpulsation creates different responses of vascular and blood flow characteristics in carotid and peripheral arteries, with more significant effects in both the carotid arteries. Additionally, the beneficial effects in ID, blood flow velocity, RI, and FR after 45 min-EECP were shown only in the patients with CAD. More importantly, acute improvement of EECP in the FR of the brachial artery was showed in males, while the FR and RI of the carotid arteries changed in females.